2005
DOI: 10.3406/psy.2005.3818
|View full text |Cite
|
Sign up to set email alerts
|

Traitements morphologiques lors de la reconnaissance des mots écrits chez des apprentis lecteurs

Abstract: Résumé Nous présentons dans cet article deux expériences portant sur les traitements morphologiques opérés par les apprentis lecteurs français lors de la lecture de mots dérivés. Les résultats de la première expérience indiquent, au moins pour les mots nouveaux, que les enfants lisent mieux (plus vite et avec moins d'erreurs) les items affixés (dégarer, construit à partir de garer) que les items pseudo-affïxés (démaner). La seconde expérience précise la nature du traitement opéré. La facilitation ne serai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 0 publications
3
22
1
6
Order By: Relevance
“…This research could also evaluate the way proximity between the two languages influences the cross-linguistic transfer of metalinguistic awareness (Deacon et al, 2007). Furthermore, a large corpus of empirical data documents the crucial impact of morphological awareness for word-decoding development as well as for reading comprehension (Baayen, Feldman & Schreuder, 2006;Carlisle, 2003;Casalis, Dusautoir, Colé & Ducrot, 2009;Casalis & Louis-Alexandre, 2000;Marec-Breton, Gombert & Colé, 2005). Then, the longitudinal evaluation of both groups during the elementary school years on morphological awareness and reading abilities will allow us to examine whether or not the bilingual advantage in morphological awareness facilitates or not the secondlanguage learners' reading learning.…”
Section: Resultsmentioning
confidence: 99%
“…This research could also evaluate the way proximity between the two languages influences the cross-linguistic transfer of metalinguistic awareness (Deacon et al, 2007). Furthermore, a large corpus of empirical data documents the crucial impact of morphological awareness for word-decoding development as well as for reading comprehension (Baayen, Feldman & Schreuder, 2006;Carlisle, 2003;Casalis, Dusautoir, Colé & Ducrot, 2009;Casalis & Louis-Alexandre, 2000;Marec-Breton, Gombert & Colé, 2005). Then, the longitudinal evaluation of both groups during the elementary school years on morphological awareness and reading abilities will allow us to examine whether or not the bilingual advantage in morphological awareness facilitates or not the secondlanguage learners' reading learning.…”
Section: Resultsmentioning
confidence: 99%
“…English-speaking second and third graders have been shown to read words with real suffixes (e.g., hilly) faster and more accurately than simple words matched for orthography (e.g., silly) (Carlisle & Stone, 2005;Laxon, Rickard, & Coltheart, 1992). Similarly, French second graders are more accurate when reading aloud pseudowords made up of morphemes (e.g., mordage, where an equivalent in English could be ''bitage'') than pseudowords with only a suffix (e.g., soumage, where an equivalent in English could be ''somage'') (Marec-Breton, Gombert, & Colé, 2005). Morphological processing in reading has also been evidenced in Hebrew morphology in third and seventh graders (Schiff, Raveh, & Kahta, 2008) and in the Italian regular orthography in third to fifth graders (Burani, Marcolini, & Stella, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The most common hypothesis is the phonological theory which suggests that difficulties experienced by dyslexics in reading new words are generally explained in terms of their poor phonological skills (Casalis, 1995;Sprenger-Charolles, Cole, Larcet, & Serniclaes 2000;Casalis, 2003;Grainger, Bouttevin, Truc, Bastien, & Ziegler 2003), especially phonemic awareness, phonological short-term memory (Snowling, 2000) and more recently, the speed of lexical access (Wolf and Bowers, 1999). Other hypotheses showed that morphological awareness had an important part in reading acquisition (Colé, Marec-Breton, Royer, & Gombert 2003;Marec-Breton, Gombert, & Colé 2005) and dyslexic children seem to over-use this capacity to compensate their difficulties in reading. Visuo-attentional hypothesis (Ans, Carbonnel, & Valdois 1998;Valdois, Bosse, Ans, Carbonnel, Zorman, & David 2003) considers that a visuo-attentional deficit can also be present in dyslexia and reduce the perceptual span.…”
Section: Introductionmentioning
confidence: 98%